Numerical Investigation of Top Coal Drawing Evolution in Longwall Top Coal Caving by the Coupled Finite Difference Method-Discrete Element Method - Yuming Huo; Defu Zhu; Zhonglun Wang; Xuanmin Song (Energies, 2021)
In longwall top coal caving (LTCC), the resource recovery ratio of the working face is directly determined by the top coal recovery ratio. An investigation of the evolution of top coal drawing characteristics and revealing the evolution of top coal drawing parameters is necessary when providing guidance for caving parameter selection and improving the top coal recovery ratio. Based on in-situ measurements of the size distribution of caved top coal blocks in Wangjialing coal mine, a finite difference method (FDM)–discrete element method (DEM) coupled method was applied to establish a “continuous–discontinuous” numerical model and the process from the first coal drawing to the common coal drawing was simulated with 17 separate working face advances. The evolution of the drawing body (DB), loose body (LB), and top coal boundary (TCB) was obtained. The results show that, the evolution of parameters of DB such as shape and size, drawing amount, length and deflection angle of the long axis of the profile ellipsoid tended to decrease first, then increase, decrease again, and finally stabilise; the increment of the LB advance coal wall distance and the coal pillar distance was close to 0 m in the common coal drawing stage, while width increment of the LB was close to the drawing interval (0.865 m). The TCB formed after each coal drawing round was fitted based on the improved “Hook” function. The evolution of height and radius of curvature of TCB’s stagnation point was analysed. This was divided into three stages: the first (first to third drawing rounds) was the initial mining influence stage, the second (fourth to ninth drawing rounds) was the transitional caving stage, and the third (after tenth drawing round) was the common coal drawing stage.